Waste-to-wealth: low-cost hard carbon anode derived from unburned charcoal with high capacity and long cycle life for sodium-ion/lithium-ion batteries. (20th November 2020) - Yu, Hai-Yue; Liang, Hao-Jie; Gu, Zhen-Yi; Meng, Yun-Feng; Yang, Miao; Yu, Meng-Xuan; Zhao, Chen-De; Wu, Xing-Long
Highlights: The unburned charcoal used in SIBs/LIBs indicates the thought of "waste-to-wealth". It is a low-cost and convenient recycling strategy. The electrode delivers high capacity and long cycle life as anode in SIBs/LIBs. Fast electrochemical kinetics and capacitive-controlled mode for good performances. Abstract: Over the past years, the biomass-derived materials are receiving more and more attention as high-performance and low-cost anodes for sodium-ion batteries (SIBs) and lithium-ion batteries (LIBs). Herein, the hard carbon derived from unburned charcoal (UC-x) is prepared by acid and heat treatment. And it is inferred from morphological characterization that the unique net structure is favorable for electrolyte permeation and charge transfer for Na + /Li + . As a result, the UC-x electrode as an anode shows high specific capacity (150 m Ah g   −   1 for SIBs and 350 m A h g   −   1 for LIBs at 0.1 A g   −   1 ) and enhanced cycling stability (250 mA h g   −   1 after 300 cycles for LIBs and 273 mA h g   −   1 after 200 cycles for SIBs). In addition, UC-1200 possesses fast electrochemical kinetics for Na + /Li + (1–6 × 10 −10 cm 2 s   −   1 for Na + and 1–2.5 × 10 −10 cm 2 s   −   1 for Li + ) and the dominated electrode reaction is mainly controlled by pseudocapacitance. In a word, this work provides a kind of unique biomass material as anodes for SIBs/LIBs from the reutilization of the waste and promotes the development of carbonaceous electrode materials. Graphical abstract: In this paper, a kind of hard carbon anode material is original from unburned charcoal for sodium-ion/lithium-ion batteries, the obtained anode materials show excellent electrochemical performance in terms of high specific capacity and long cycle life. Such application for bio-waste enhances the thought of "waste-to-wealth". Image, graphical abstract